2012
DOI: 10.2527/jas.2012-5064
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between rumination time, metabolic conditions, and health status in dairy cows during the transition period

Abstract: The main objective of this experiment was to monitor the rumination pattern during the transition period in primiparous (PR) and pluriparous (PL) dairy cows and to investigate its relationships with metabolic conditions, milk yield, and health status. The study was carried out in an experimental free-stall barn and involved 32 Italian Friesian cows (9 PR and 23 PL) during the transition phase. The rumination time (RT) was recorded with an automatic system (HR-Tag), and data were calculated and summarized in 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
89
8
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(131 citation statements)
references
References 37 publications
23
89
8
11
Order By: Relevance
“…Further, lower eating period in dams with low MBS might be due to more number of primiparous animals experienced more parturition stress. Results of this study indicated shortest rumination period during the early post calving stage which is supported by Soriani et al (2012) who reported decrease in rumination time on the day of calving. Further, Pahl et al (2014) observed depressed rumination in first 8 h of after calving.…”
Section: Discussionsupporting
confidence: 84%
“…Further, lower eating period in dams with low MBS might be due to more number of primiparous animals experienced more parturition stress. Results of this study indicated shortest rumination period during the early post calving stage which is supported by Soriani et al (2012) who reported decrease in rumination time on the day of calving. Further, Pahl et al (2014) observed depressed rumination in first 8 h of after calving.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, the negative energy balance condition at the end of gestation could be worsened by the decrease of feed intake around the parturition (Xiccato, 1996) which induces hypoinsulinaemia in does (Brecchia et al, 2006), preventing the use of glucose as energy source and consequently the increase of lipid catabolism and NEFA concentrations (Rebollar et al, 2011). In our study, the plasma level of creatinine was higher before parturition and decreased after parturition likely due to muscle protein mobilization or catabolism as observed also in dairy cows (Bertoni et al, 1994;Soriani et al, 2012).…”
Section: Effect Of Transition Period In Reproductive Rabbit Doessupporting
confidence: 68%
“…Debates of how to predict and identify ill animals in a herd, and how to apply preventive veterinary practices are active topics of research [16]. After the indications that rumination behavior may be a promising indicator of metabolic conditions, new methods to measure and evaluate herd performance have typically focused on feeding comportment in ruminants [30]. Therefore, the introduction of a novel method to indirectly measure RT, evaluates vocal signs and allows automatic measurement of RT to analyze rumination behavior in different environments [13,22].…”
Section: Measurements Of Cow Behavior Identify Animals At Risk For Ilmentioning
confidence: 99%
“…Therefore, the introduction of a novel method to indirectly measure RT, evaluates vocal signs and allows automatic measurement of RT to analyze rumination behavior in different environments [13,22]. Results of these studies found that cows with different health problems ruminate less then healthy cows, and therefore, there is a relationship between RT and metabolic conditions such as ketosis, hypocalcemia, and inflammatory blood markers around calving [13,14,22,30].…”
Section: Measurements Of Cow Behavior Identify Animals At Risk For Ilmentioning
confidence: 99%